Splinting is effective for night-only symptomatic carpal tunnel syndrome patients - Niftaliyev, Elvin; Asil, Talip; Kendirli, Tansel; Halac, Gulistan; Yucel, Hulya; Kocaman, Gulsen; Demir, Saliha; Duruyen, Humeyra (Journal of Physical Therapy Science, 2015)
[Purpose] Carpal tunnel syndrome is the most common entrapment neuropathy of the median nerve. Splinting is one of the most used conservative treatment methods for carpal tunnel syndrome. The aim of this study was to show the effectiveness of splinting in carpal tunnel syndrome patients who were divided into two groups according to their level of symptoms. [Subjects and Methods] A total of 40 carpal tunnel syndrome patients were divided into 2 groups based on having symptoms only at night or during the day were included in this study. These two groups were compared at the end of a 3-months splinting therapy in terms of improvement of severity of symptoms, functional capacity, pain level, and electrophysiological findings. [Results] Pain levels of both groups were similar at baseline. After splinting, pain levels of night-only symptomatic patients were lower than those of sustained symptomatic ones. No differences were found in symptom severity, functional capacity, and the electrophysiological findings in either group after the splinting. [Conclusion] The results of this study show that splinting alone may be sufficient to decrease the pain for night-only symptomatic patients. Combined therapy methods may be needed for sustained symptomatic patients.